Large variation in ESBL-producing Escherichia coli carriers in six European countries including Russia - Ny S (My University, 2022)
We investigated the faecal carriage prevalence of extended-spectrum β-lactamase production in Escherichia coli (EP-EC) and/or Klebsiella pneumoniae (EP-KP) and risk factors associated with carriage among adult study subjects in Finland, Germany, Latvia, Poland, Russia and Sweden (partner countries). The aim was to get indicative data on the prevalence of ESBL-carriage in specific populations in the region. Faecal samples were collected from four study populations and screened on ChromID-ESBL and ChromID-OXA-48 plates. Positive isolates were further characterised phenotypically. Our results show a large variation in carrier prevalence ranging from 1.6% in Latvia to 23.2% in Russia for EP-EC. For the other partner countries, the prevalence of EP-EC were in increasing numbers, 2.3% for Germany, 4.7% for Finland, 6.6% for Sweden, 8.0% for Poland and 8.1% for all partner countries in total. Carriers of EP-KP were identified only in Finland, Russia and Sweden, and the prevalence was < 2% in each of these countries. No carriers of carbapenemase-producing isolates were identified. This is the first study reporting prevalence of carriers (excluding traveller studies) for Finland, Latvia, Poland and Russia. It contributes with important information regarding the prevalence of EP-EC and EP-KP carriage in regions where studies on carriers are limited.